2007
DOI: 10.1148/radiol.2432060120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SPIO and USPIO for in Vitro Labeling of Human Monocytes: MR Detection and Cell Function

Abstract: In vitro labeling of human monocytes is effective by using SPIOs, not USPIOs. Incubation with SPIOs (1.0 mg Fe/mL) results in efficient labeling detectable on MR images and does not affect cellular viability and activation markers such as cell migration and cytokine production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 27 publications
7
106
0
Order By: Relevance
“…Although MPIO was excluded from all of these studies, it was found that phagocytic monocytes are more effectively labeled with SSPIO (150 nm) compared with USPIO (30 nm) [18,29]. Further, it was found that ionic carboxydextran-coated SSPIO (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although MPIO was excluded from all of these studies, it was found that phagocytic monocytes are more effectively labeled with SSPIO (150 nm) compared with USPIO (30 nm) [18,29]. Further, it was found that ionic carboxydextran-coated SSPIO (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…19 Particles with larger diameters were more efficiently incorporated into macrophages. 21,22 istration, there were no differences in labeling efficiencies between ATDM at 28 nm and at 74 nm ( Figure 3A).…”
Section: Discussionmentioning
confidence: 97%
“…All USPIO particles were dissolved in the cell growth medium at a concentration of 0.3 mg Fe/mL, which is similar to the concentration used in another published report. 18 Cells (2 × 10 6 ) were incubated with medium containing USPIO particles for 1, 2, or 4 h (same time points noted in a previous report) 19 at 37°C under 5% CO 2 . After incubation, the medium was removed by two washes with phosphatebuffered saline (PBS) followed by fixation of the cells for 30 min with 7.5% formalin.…”
Section: Measurement Of Uspio-labeling Efficiencymentioning
confidence: 99%
“…Several groups have investigated the effects of particle size and iron concentration on SPIO and USPIO uptake rates. In comparison with USPIOs, macrophages and monocytes appear to have much a higher uptake preference for SPIOs and are more effectively labeled by the latter [76,77]. Thorek et al [78] tested the uptake rate of different sized SPIOs in non-phagocytic T-cells and showed that particles <300 nm were most efficient in cell labeling.…”
Section: Fig 5 Cd8mentioning
confidence: 99%